DUSP10 upregulation is a poor prognosticator and promotes cell proliferation and migration in glioma - Zhou, Fang; Zeng, Lingfeng; Chen, Xi; Zhou, Fan; Zhang, Zhen; Yuan, Yixiao; Wang, Heping; Yao, Huayi; Tian, Jintao; Liu, Xujie; Zhao, Jinxi; Huang, Xiaobin; et al. (Frontiers in Oncology, 2023)
Dual-specificity phosphatase 10 (DUSP10) is correlated with inflammation, cytokine secretion, cell proliferation, survival, and apoptosis. However, its role in glioma unclear. In this finding, we sought to examine the expression as well as its carcinogenic mechanisms of DUSP10 in glioma. We found that DUSP10 expression in glioma was significantly higher than those in normal brain tissues. High DUSP10 expression indicated adverse clinical outcomes in glioma patients. Increased DUSP10 expression was correlated with clinical features in glioma. Univariate cox analysis showed that high DUSP10 expression was a potential independent marker for poor prognosis in glioma. Furthermore, we uncover that DUSP10 expression in glioma was negative correlated with DNA methylation levels of DUSP10. DNA methylation level of DUSP10 also negatively related to poor prognosis in glioma. More importantly, DUSP10 expression was positively correlated with the infiltration of B cells, CD4+T cells, CD8+T cells, neutrophils, macrophages, and dendritic cells in glioma. KEGG and GSEA enrichemnt analysis confirmed that DUSP10 may participate in signaling pathways involved in focal adhesion, TNF signaling pathway, Th17 cell differentiation, NF-kappa B signaling pathway. Finally, we uncover that DUSP10 was dramatically up-regulated in GBM cells and knockdown of DUSP10 inhibited tumor cell proliferation and migration. Our findings confirmed that DUSP10 may serve as a potential prognostic biomarker in glioma.